GAMBARAN PENGETAHUAN IBU HAMIL TENTANG PREEKLAMPSI 2020 - Safitri Safitri (Politeknik Kesehatan Kemenkes Bandung, 2020)
This literature study is motivated by the high MMR in 2015 of 303 per 100,000 live births caused by 30% bleeding, preeclampsia 27.1%, infections 7.3%. Lampake Samarinda health center obtained 26 cases of preeclampsia from 329 pregnant women during 2016. There were 45 cases of MMR in Indramayu District with 11 cases of hypertension in pregnancy in 2017. There were 9 cases of MMR in Cimahi which were dominated by maternal and maternal deaths in 2012. There are 29 cases of MMR in 2018 in Bandung. Preeclampsia is a complication of a continuing pregnancy with the same cause, therefore prevention or early diagnosis can reduce the incidence. This literature study aims to find out the description of knowledge of pregnant women about preeclampsia. The type of this research is descriptive qualitative using systematic literature review method by analyzing 3 journals of health or nursing research about preeclampsia that have existed in the range 2009-2019. The results of the analysis show that the three journals used have in common namely the majority of the age of pregnant women at 20-35 years, the level of education ≤ high school and the knowledge of pregnant women about preeclampsia at a sufficient level. Some are in accordance with the theory of knowledge and preeclampsia and some are not in accordance with the theory. Recommendations to institutions, hopefully this literature study will be an additional information and scientific reference.